2017
DOI: 10.1177/0731684417712070
|View full text |Cite
|
Sign up to set email alerts
|

The potential of kaolin as a reinforcing filler for rubber composites with new sulfur cure systems

Abstract: The effect of a large amount of kaolin (China clay) on the viscosity, cure, hardness, Young’s modulus, tensile strength, elongation at break, stored energy density at break, tear energy and compression set resistance of some sulfur-cured natural rubber, polybutadiene rubber and ethylene-propylene-diene rubber composites was investigated. The kaolin surface had been pre-treated with 3-mercaptopropyltrimethoxysilane to improve its dispersion in the rubbers. For natural rubber, the hardness and Young’s modulus im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…The type of clay in this study is kaolin clay, as described in Figure 8. The use of clay as a rubber filler has been studied by many researchers, including Goodman and Riley (2012), Ismail and Mathialagan (2011), Lalikova et al (2011), Ruamcharoen et al (2014, Szustakiewicz et al (2013), Zhang et al (2012), and Zhang et al (2010, and modified clay has also been widely examined-for example, in the work by Ambre et al (2008), Jagtap et al (2013), Kord et al (2017), Ogbebor et al (2015aOgbebor et al ( , 2015b, Peter et al (2016), Puglia et al (2016), Saritha et al (2012), Sheikh et al (2017), Sreelekshmi et al (2016Sreelekshmi et al ( , 2017, Sukumar and Menon (2008), and Yahaya et al (2009). Most of the types of clay used by researchers are kaolin clay, in addition to bentonite and montmorillonite clay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of clay in this study is kaolin clay, as described in Figure 8. The use of clay as a rubber filler has been studied by many researchers, including Goodman and Riley (2012), Ismail and Mathialagan (2011), Lalikova et al (2011), Ruamcharoen et al (2014, Szustakiewicz et al (2013), Zhang et al (2012), and Zhang et al (2010, and modified clay has also been widely examined-for example, in the work by Ambre et al (2008), Jagtap et al (2013), Kord et al (2017), Ogbebor et al (2015aOgbebor et al ( , 2015b, Peter et al (2016), Puglia et al (2016), Saritha et al (2012), Sheikh et al (2017), Sreelekshmi et al (2016Sreelekshmi et al ( , 2017, Sukumar and Menon (2008), and Yahaya et al (2009). Most of the types of clay used by researchers are kaolin clay, in addition to bentonite and montmorillonite clay.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of chemicals have been used by researchers to modify clay, such as the metal chlorides used by Lalikova et al (2011), the fatty acid salt used by Zhang et al (2014), the hydrazine hydrate used by Sukumar and Menon (2008), the dimethyl, benzyl, dehydrogenated tallow, and quarternary ammonium used by Saritha et al (2012), the 3mercaptoprophyltrimethoxysilane used by Sheikh et al (2017), the hexamethylenediamine used by Sreelekshmi et al (2017), the dimethyldioctadecylammonium and bis(4hydroxybuthyl)methyldioctadecylammonium used by Nam et al (2004), and the octadecylamine used by Praveen et al (2009), Nigam et al (2012), and Manchado et al (2003). In general, this clay modification aims to increase the adsorption on the clay surface so that the clay can function better as a filler.…”
Section: Introductionmentioning
confidence: 99%
“…This can be employed in compound development for rubber industry. 8 Several attempts have been made to investigate the effect of adding CB on the properties of NR. [9][10][11] It was reported that the CB-filled NR samples take up a lower amount of aromatic hydrocarbons than silica-filled ones.…”
Section: Introductionmentioning
confidence: 99%
“…Among nanofillers, clay minerals such as montmorillonites (Mts) have been of interest for the development or improvement of composite material properties due to their availability, low cost, and rich chemistry on their surfaces . Mts have a 2:1 layer structure.…”
Section: Introductionmentioning
confidence: 99%
“…The primary concern in preparing clay nanocomposites is to attain a very high degree of dispersion of clay aggregates that afford very large surface areas, exhibiting significant improvements in physical, mechanical and thermal properties in relation to the polymer host . Three different levels of interactions between clays and polymer chains can be identified within a polymer matrix: non‐exfoliated, intercalated and exfoliated .…”
Section: Introductionmentioning
confidence: 99%